INTERNALISASI BUDAYA SEKOLAH ISLAMI DI ACEH - Saminan Saminan (SCAD Independent, 2015)
Educational practices, including religious education in Aceh so far, still oriented to the chase and collect scientific information as much as possible, but not the fundamental aspects of education. Which is how the next generation is able to live a full life and life to lean towards the values of the Divine. Aceh province with special education, customs and culture and have the Qanun on Islamic education should immediately formulate or searching the threads of how real the concept of cultured Islamic school in accordance with the nature and purpose of Islamic education. In the context of this study, core values that will be the focus of study in the development of Islamic school culture is the internalization of Islamic values derived from the Quran and Sunnah and the core values that became a national education goals and strategic vision of education in the province.